Impact of a supportive text messaging program (Text4Support) for mitigating psychological problems in patients receiving formal mental health services: A randomized controlled trial - Gloria Obuobi-Donkor; Reham Shalaby; Belinda Agyapong; Samuel Obeng Nkrumah; Medard Kofi Adu; Ejemai Eboreime; Lori Wozney; Vincent Israel Opoku Agyapong (Digital Health)
Background Text-based interventions are an innovative way to bridge gaps in mental health care. Programs like Text4Support provide accessible, cost-effective mental health support using daily messages based on cognitive behavioral principles, reaching a broad population. Objective The study aims to evaluate the effectiveness of Text4Support in improving mental health outcomes compared to usual care in patients receiving formal mental health services. Methods A randomized controlled trial was conducted on participants attending community mental health programs and those recently discharged from psychiatric inpatient and emergency care in Nova Scotia, Canada. Participants were assigned to either the Text4Support or control group. Mental health conditions were measured using validated scales. Patients in the Text4Support group received daily supportive text messages, whilst the control group received a single text message with a link to the Nova Scotia Health e-mental health resources. Results Seven hundred eighty-one eligible patients were randomized, and 307 were included in the analysis. After adjusting for baseline scores, the third and ninth questions of the PHQ-9 showed a significant difference between the Text4Support group and the control group. When results were assessed based on self-reports from control group participants as to whether they accessed or did not access the NS Health e-mental health resource link, significant differences between the three groups were noted, with improvements for suicidal and/or self-harm ideation and disturbed sleep in the Text4Support group and deterioration observed in the two control groups. Conclusion Text4Support addresses critical psychological symptoms like sleep disturbances and suicidal and/or self-harm ideation during vulnerable periods in patients’ mental health journeys. Text4Support is a promising adjunct to conventional mental health care. Trial registration ClinicalTrials.gov (NCT05411302). Registered on 6 June 2022.